Collaborative Strategic Model of Creative Economy Actors and the Halal Industry in Accelerating International Market Penetration in Pekalongan - Salma Nabila; Moses Adeolu AGOI; Kuat Ismanto (Journal of Management, Finance, and Accounting Research, 2026)
The global halal industry has shifted towards fashion, offering vast opportunities for Pekalongan's creative economy. However, despite its status as a UNESCO Creative City, the export of Pekalongan's creative products (crafts and batik) is hindered by MSMEs' low literacy regarding halal value chain standards and critical contamination risks during production. Previous studies have mostly treated the creative economy and halal industry separately, leaving a significant gap in integrative frameworks. Addressing this research gap, this study aims to construct a strategic collaboration model among stakeholders to overcome these export barriers. Using an exploratory qualitative case study method, primary data were gathered through in-depth interviews with key Pentahelix elements—namely government, academia, business, community, and media. The results indicate that integrating comparative cultural advantages with competitive halal compliance through the Pentahelix model triggers value co-creation. This synergy empowers the government as a regulatory catalyst, academia in material innovation, businesses as export aggregators, communities as ethical supervisors, and media for digital branding. This collaboration fosters the "Halal and Ethical Modest Fashion" concept, effectively increasing global market competitiveness. Theoretically, this study contributes to the strategic management literature within the halal ecosystem. Practically, it contributes by recommending local governments to establish a dedicated task force integrating halal certification into the creative economy export roadmap. [Industri halal global telah merambah sektor fesyen, menawarkan peluang besar bagi ekonomi kreatif Pekalongan. Namun, meskipun berstatus sebagai Kota Kreatif UNESCO, ekspor produk kreatif Pekalongan (kriya dan batik) terhambat oleh rendahnya literasi UMKM mengenai standar rantai nilai halal serta adanya risiko kontaminasi kritis pada proses produksi. Penelitian-penelitian sebelumnya sebagian besar masih memisahkan kajian ekonomi kreatif dan industri halal, sehingga menyisakan celah penelitian (research gap) pada kurangnya kerangka kerja integratif. Berangkat dari kesenjangan tersebut, penelitian ini bertujuan untuk mengkonstruksi model kolaborasi strategis antar pemangku kepentingan guna mengatasi hambatan ekspor tersebut. Menggunakan metode studi kasus kualitatif eksploratif, data primer dikumpulkan melalui wawancara mendalam dengan elemen kunci Pentahelix—yakni pemerintah, akademisi, bisnis, komunitas, dan media. Hasil penelitian menunjukkan bahwa integrasi keunggulan komparatif (budaya) dengan keunggulan kompetitif (kepatuhan halal) melalui model Pentahelix mampu memicu penciptaan nilai bersama (value co-creation). Sinergi ini memberdayakan pemerintah sebagai katalisator regulasi, akademisi dalam inovasi material, bisnis sebagai agregator ekspor, komunitas sebagai pengawas etika, dan media untuk branding digital. Kolaborasi ini mendorong lahirnya konsep "Halal and Ethical Modest Fashion" yang secara efektif meningkatkan daya saing pasar global. Secara teoretis, penelitian ini berkontribusi pada literatur manajemen strategis dalam ekosistem halal. Secara praktis, penelitian ini berkontribusi dengan merekomendasikan pemerintah daerah untuk membentuk satuan tugas khusus guna mengintegrasikan sertifikasi halal ke dalam peta jalan ekspor ekonomi kreatif.]